Effect of Sous Vide Technique and Nitrite on Qualities of Golek Chicken Product - ภักดีฉนวน พัชรินทร์; ศุภอักษร ประกายแก้ว; สร้อยสน ใบศรี; หนูเมือง ชุมพร (KKU Science Journal, 2017)
Sous vide (SV) is a technique that food is sealed in a vacuum condition and then pasteurized. This research compared SV technique and addition of sodium nitrite 4 treatments as follow: T1) Control, T2) non SV/0.02 % of NaNO2, T3) SV 70°C for 2 min/NaNO2 and T4) SV 70°C for 2 min/NaNO2 on changes of microorganisms, pH, shearforce value, microstructure of meat fiber and sensory qualities during 60 days of storaging at 4°C. The experiments found that golek chicken product without SV (T1 and T2) detected yeast and mold by the end of storaging and had higher oxidation than the SV treatments (T3 and T4). In addition, the product in T4 had higher sensory liking scoring than others. Therefore, it can be concluded that using of Sous vide at 80°C for 2 min with 0.02% of NaNO2 lead the product had longer shelf life than 60 days at 4°C. The product had qualities under the regulation of Thai community product standard of seasoned chicken (TCPS 755/2548) and proper to apply in commercial.